Do Mothers and Fathers in Germany Really Prefer a Traditional Division of Labor? The Impact of Working Hours on Life Satisfaction Reconsidered - Heyne, Stefanie; Wolbring, Tobias (Zeitschrift für Soziologie, 2022)
This study critically reexamines previous results on the effects of working hours on life satisfaction. First, we replicate the original results which suggest that a traditional division of labor maximizes fathers' and mothers' well-being. Loosening parametric restrictions, avoiding confounding by childbirth, and taking East-West differences into account in a second step, we find that (1) fathers are most satisfied when working between 35 and 60 hours per week, (2) mothers are more satisfied with their life when working at least -25 hours per week as compared to not working, and (3) different arrangement of labor division among mothers and fathers lead to similar levels of life satisfaction. Thus, in contrast to what has been suggested by the original study, our replication reveals that the male breadwinner model is not the sole way to maximize parents' well-being.
CRIS-Team WoS Importer:2022-09-09
Keywords: Gender